High‐resolution 40Ar/39Ar dating using a mechanical sample transfer system combined with a high‐temperature cell for step heating experiments and a multicollector ARGUS noble gas mass spectrometer. (6th June 2014) - Pfänder, Jörg A.; Sperner, Blanka; Ratschbacher, Lothar; Fischer, Albrecht; Meyer, Martin; Leistner, Martin; Schaeben, Helmut
Abstract 40Ar/39Ar dating of young (<1 Ma) and/or low potassium samples requires degassing of large amounts of material either by a laser or a furnace. A furnace excels in precise and reproducible temperature control and in providing a homogeneous temperature distribution even for relatively large sample amounts. For most systems, however, the degassed mineral or whole‐rock residues remain in the crucible after measurement. This reduces the thermal conductivity and increases the blank levels and baking times. To mitigate these problems, we combined a mechanical sample transfer system with a low volume (∼90 mL) high‐temperature cell. The system operates under ultrahigh vacuum and uses Mo‐crucibles, in which up to 1000 mg of sample is transferred into the furnace and taken out after degassing. The system has short baking times (20–30 min), highly reproducible heating conditions and an overall low blank level due to the absence of silicate (glassy) sample residue in the main crucible of the furnace. The system interconnects through a gas purification line with a low volume, high sensitivity multicollector ARGUS noble gas mass spectrometer. Intraday reproducibility of 40Ar/36Ar ratios measured on air aliquots of >5 × 10−16 mol 36Ar is better than 0.5‰–1.0‰ (1σ, n = 4–8). We illustrate the system performance by 40Ar/39Ar dating of whole‐rock samples and mineral separates from the Oman ophiolite as well as from the Siebengebirge, Heldburg, and Rhön volcanic provinces in Central Germany.